Vibro-acoustic behavior of metallic foam doubly-curved plates. (2022) - Reddy, R. Kiran Kumar; George, Nivish; Mohan, Sreejith; Bhagat, Vinod; Arunkumar, M.P.
Abstract: When compared to flat and single curved structural elements, doubly curved structural elements have a higher membrane energy. Porous materials are being used in a wide range of engineering applications to minimize the overall weight of the structure. However, the reduced weight of the structures produces high levels of noise and vibration. The amount of increased noise and vibration levels caused by introducing porosity into structures must be evaluated. The main objective of the present study is to demonstrate the vibro-acoustic behavior of solid and porous doubly-curved plates subjected to arbitrary boundary conditions using the ANSYS Finite elemental (FE) software. In the designer module, a doubly-curved plate is modelled, and the relevant boundary conditions are supplied. To determine the free and forced vibrational behavior of the doubly-curved plates, modal and harmonic analyses are performed. Finally, uncoupled acoustic analysis is being used to obtain the acoustic behavior of the structure by importing the normal velocity obtained in harmonic analysis as a boundary condition. The effect of porosity and arbitrary boundary conditions on the acoustic behavior of doubly-curved plates is briefly studied. The obtained findings show that the difference in radiated sound power level between solid and porous doubly-curved plates is relatively insignificant. As a result, porous doubly-curved plates are recommended for low-weight applications without compromising on its vibro-acoustic behavior.